Weight as predictors of clinical progression and treatment failure: Results from the TREAT Asia Pediatric HIV observational database - Kariminia A. (Lippincott Williams and Wilkins, 2014)
Objective: To evaluate the value of time-updated weight and height in predicting clinical progression, and immunological and virological failure in children receiving combination antiretroviral therapy (cART). Methods: We used Cox regression to analyze data of a cohort of Asian children. Results: A total of 2608 children were included; median age at cART was 5.7 years. Time-updated weight for age z score <-3 was associated with mortality (P < 0.001) independent of CD4% and <-2 was associated with immunological failure (P ≤ 0.03) independent of age at cART. Conclusions: Weight monitoring provides useful data to inform clinical management of children on cART in resource-limited settings. © 2014 by Lippincott Williams & Wilkins.